Prescribing medications to children - a GP’s view - Simmons, Amanda (Henry Stewart Talks, 2018)
The issue of compliance in children, Consultation time as a key resource in the assessment for children, The effects of available online information and media on parents’ decisions, Attention deficit disorders, Refusal of parents to vaccinate their children, The importance of proper clinician-parent communication, How can pharmaceutical companies help increase compliance in children